Virtual 4DCT from 4DMRI for the management of respiratory motion in carbon ion therapy of abdominal tumors. Issue 3 (20th January 2020) - Meschini, Giorgia; Vai, Alessandro; Paganelli, Chiara; Molinelli, Silvia; Fontana, Giulia; Pella, Andrea; Preda, Lorenzo; Vitolo, Viviana; Valvo, Francesca; Ciocca, Mario; Riboldi, Marco; Baroni, Guido
Abstract : Purpose: To evaluate a method for generating virtual four‐dimensional computed tomography (4DCT) from four‐dimensional magnetic resonance imaging (4DMRI) data in carbon ion radiotherapy with pencil beam scanning for abdominal tumors. Methods: Deformable image registration is used to: (a) register each respiratory phase of the 4DMRI to the end‐exhale MRI; (b) register the reference end‐exhale CT to the end‐exhale MRI volume; (c) generate the virtual 4DCT by warping the registered CT according to the obtained deformation fields. A respiratory‐gated carbon ion treatment plan is optimized on the planning 4DCT and the corresponding dose distribution is recalculated on the virtual 4DCT. The method was validated on a digital anthropomorphic phantom and tested on eight patients (18 acquisitions). For the phantom, a ground truth dataset was available to assess the method performances from the geometrical and dosimetric standpoints. For the patients, the virtual 4DCT was compared with the planning 4DCT. Results: In the phantom, the method exhibits a geometrical accuracy within the voxel size and Dose Volume Histograms deviations up to 3.3% for target V95% (mean dose difference ≤ 0.2% of the prescription dose, gamma pass rate > 98%). For patients, the virtual and the planning 4DCTs show good agreement at end‐exhale (3% median D95% difference), whereas other respiratory phases exhibit moderate motion variability with consequent dose discrepancies, confirming the need for motion mitigation strategies during treatment. Conclusions: The virtual 4DCT approach is feasible to evaluate treatment plan robustness against intra‐ and interfraction motion in carbon ion therapy delivered at the abdominal site.